Determinants of foreign direct investment in India and retail sector liberalization: a GMM estimation - Manocha, R. (International Journal of Accounting & Business Finance, 2023)
India has one of the largest retail markets in the world. In order to channelize the huge potential of Indian retail sector and to provide best of the cosmopolitan culture to the fast-growing Indian retail market and to stimulate India’s FDI inflows, the Government of India has systematically liberalized FDI in the retail sector since 2006. The present study incorporates retail sector liberalization measures as one of the institutional changes and tries to empirically examine the impact of institutional changes on India’s FDI inflows. Along with the conventional determinants of FDI, extended institutional variable has been incorporated in order to study the inflows from 21 investing countries for the period 2001-2020. The results were captured by employing fixed effects, random effects, and GMM (two-step) estimation. The study suggested a positive and significant coefficient for extended market size, economic freedom index, and extended institutional variable whereas inflation was found to have a significant and negative impact on India’s FDI inflows.
Keywords: FDI; Retail Sector; GMM Estimation; Institutional Measures